Advanced UHPLC-MS/MS method development for ultra-low level quantitative analysis of analytes in agricultural matrices - Kompalage, Kushan Pamoda Kompale (My University, 2026)
Advanced ultra-high-performance liquid chromatography–tandem mass spectrometry (UHPLC–MS/MS) methods were developed and optimized for ultra-low-level quantitative analysis of analytes in agricultural and biological matrices. The work focused on improving chromatographic efficiency, analytical sensitivity, selectivity, and quantitative reliability through optimized sample preparation, chromatographic separation, and tandem mass spectrometric detection for applications involving veterinary pharmaceuticals and per- and polyfluoroalkyl substances (PFAS). Foundational chapters established the scientific and analytical importance of monitoring trace-level contaminants in agricultural environments. Agricultural matrices, including agricultural well water, soil, biosolids, plant tissue, and animal blood, were examined in the context of environmental contamination, veterinary pharmacokinetics, food safety, and regulatory compliance. Particular emphasis was placed on matrix-specific analytical challenges, including PFAS background contamination, analyte sorption, matrix suppression, protein and lipid interference, and ultra-low-level detection requirements. Regulatory monitoring frameworks for PFAS and veterinary pharmaceutical residues further underscore the growing need for sensitive, reproducible analytical methods capable of quantifying these analytes in complex agricultural matrices. Fundamental principles of UHPLC–MS/MS method development were investigated to establish the analytical framework for trace-level quantitative analysis. Chromatographic concepts, including chromatographic resolution, band broadening, retention behavior, column efficiency, and the van Deemter relationship, were evaluated in relation to modern UHPLC systems utilizing sub-2 [mu]m particle technology. Theoretical and applied aspects of electrospray ionization, tandem mass spectrometry, quadrupole mass analysis, and multiple reaction monitoring (MRM) were examined to demonstrate how optimized instrumental conditions improve analytical performance. Strategies involving stationary-phase selection, solvent optimization, gradient development, solid-phase extraction, derivatization, and isotope dilution calibration were investigated as essential components of robust UHPLC–MS/MS workflows for agricultural and biological samples. Several targeted UHPLC–MS/MS assays were developed and validated for veterinary pharmaceutical analysis in animal plasma matrices. A multianalyte method was established for the simultaneous quantification of azaperone, trazodone, and gabapentin in porcine plasma. A separate UHPLC–MS/MS method was developed for quantifying flunixin in ovine plasma to support pharmacokinetic investigations in sheep. An additional multianalyte assay was developed to concurrently quantify meloxicam, flunixin, and firocoxib in goat plasma. Sample preparation procedures involving protein precipitation and solid-phase extraction were optimized to minimize matrix interferences and improve analyte recovery. The developed methods demonstrated strong linearity, sensitivity, accuracy, and precision suitable for veterinary pharmacokinetic investigations and residue analysis. Advanced PFAS analytical workflows were also established, using EPA Method 1633A as the primary framework for agricultural well-water analysis in Kansas. UHPLC–MS/MS conditions, isotope dilution calibration, contamination-control procedures, and extraction workflows were optimized for targeted PFAS analysis at ultra-low concentrations. Analytical workflows were developed for PFAS determination in agricultural matrices, including water, soil, biosolids, plant tissue, and biological samples; however, the present work focused specifically on agricultural well water samples. Advanced chromatographic data evaluation demonstrated the importance of careful peak integration and post-acquisition review for reliable PFAS quantification near reporting thresholds. Collectively, the developed UHPLC–MS/MS methodologies provide sensitive, selective, and reproducible analytical platforms for ultra-low-level quantitative analysis of pharmaceutical compounds and PFAS in agricultural and biological matrices. The findings further demonstrate the critical role of advanced chromatographic and tandem mass spectrometric techniques in modern agricultural, veterinary, and environmental analytical chemistry.
Keywords: Agriculture; Tandem mass spectrometry; Liquid chromatography; Per- and polyfluoroalkyl substances; Veterinary drugs